INDIKATOR KELUARGA SEHAT DI KELURAHAN LEBAK BANDUNG KOTA JAMBI - Cici Sahara; Mila Triana Sari (Universitas Baiturrahim, 2017)
Background: Indicators of Healthy Families is an indicator / labeling of the health status of the family. Family declared healthy families if they meet 12 indicators of a healthy family that consists of a family planning program, pregnant women antenatal check (ANC) according to standards, Babies get complete immunization, exclusive breastfeeding infants 0-6 months, growth monitoring Toddler, Tuberculosis Patients according to the standard treatment, patients regularly treated hypertension, severe Mental Disorder Patients treated, there is no family member who smokes, Having Means Water, Using latrines healthy, and A family is already a member of the National Health Insurance (JKN). The purpose of this research is to know the description of indicators of healthy families in the village of Lebak Bandung city of Jambi.Methods: This research is a quantitative descriptively. The samples on this research 65 KK through the technique of